Review of Comparative Perspectives on Social Movements: Political Opportunities. Mobilizing Structure, and Cultural Framings (Book) - Kleidman, Robert (1999)
Reviews the book Comparative Perspectives on Social Movements: Political Opportunities, Mobilizing Structure, and Cultural Framings, edited by Doug McAdam, John D. McCarthy, and Mayer N. Zald